2010
DOI: 10.1177/154230501006400102
|View full text |Cite
|
Sign up to set email alerts
|

In the Beginning: A Canadian Ethnographic Study on Sources and Definitions of Spiritual Reflection Used by Health Care Professionals Who are Not Chaplains

Abstract: This qualitative study presents a literature review, methodology, findings and discussion from a sample of 20 health care professional around their experiences of sources and definitions of spiritual reflection. The sample includes nursing, social work, occupational therapy, medicine, physiotherapy, music therapy, psychology and recreational therapy. Major sources are music, poetry, stories and sacred texts. Definitions are meaning making and encountering the divine along with personal reflection on values and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Ethnographic approaches to qualitative research are identified in 2 articles (5%) and are described as research on a particular group that constitutes a particular culture (O’Connor et al., 2010; see Table 3). While both articles present research that focuses on particular groups or cultures and utilize all the central elements of ethnography, it is unclear as to the extent to which either of these studies constitutes an ‘ethnography’ as defined by cultural anthropology and adapted by pastoral practitioners (McClintock-Fulkerson, 2007; Moschella, 2008, Wigg-Stevenson, 2014).…”
Section: Findings: Quantity Types and Rigor Of Qualitative Research mentioning
confidence: 99%
See 1 more Smart Citation
“…Ethnographic approaches to qualitative research are identified in 2 articles (5%) and are described as research on a particular group that constitutes a particular culture (O’Connor et al., 2010; see Table 3). While both articles present research that focuses on particular groups or cultures and utilize all the central elements of ethnography, it is unclear as to the extent to which either of these studies constitutes an ‘ethnography’ as defined by cultural anthropology and adapted by pastoral practitioners (McClintock-Fulkerson, 2007; Moschella, 2008, Wigg-Stevenson, 2014).…”
Section: Findings: Quantity Types and Rigor Of Qualitative Research mentioning
confidence: 99%
“…In terms of our second criteria -- researcher reflexivity -- 5 of 34 studies (14.7%) intentionally identify researcher reflexivity (O’Connor et al., 2010; Ashby & Verner, 2010; Pan, Chang, Jiang, & Lee, 2012; Marsay, 2013; Snodgrass, 2014). Each of these describes aspects of the researchers’ experiences and locations that affect and shape the focus of research.…”
Section: Assessing Quality Of Qualitative Articlesmentioning
confidence: 99%